Laser Acupuncture as a Treatment Option for Carpal Tunnel Syndrome Management: a Case Series - Iwan Limanjaya; Salim Haris; Irma Nareswari (Medical Association of Pharmacopuncture Institute, 2022)
Carpal tunnel syndrome (CTS) is disease that gives burdens for many countries, with a few choices for the management such as drugs or surgery, each has side effects that decrease the quality of life. Acupuncture is proven to be an effective treatment for pain and can restore nerve functions, and laser acupuncture is one of the modalities. This study aims to assess the effectiveness of laser acupuncture with total sample of 3 patients (6 wrists) mostly with tingling sensations and the outcomes are Boston questionnaire (BCTQ), visual analogue scale (VAS), Tinel sign, Phalen sign, and parameters of nerve conduction study (NCS). Acupuncture points used here are PC6, PC7, EXUE9, and LI4. The results show a decrease in NCS grades for 3 wrists, all wrists have BCTQ score improvements, a decrease in VAS, but no significant improvement in Tinel and Phalen signs. It is concluded that laser acupuncture can be used as a treatment option for the management of carpal tunnel syndrome.